A PHBA-functionalized organic-inorganic hybrid polyoxometalate as a luminescent probe for selectively sensing chromium and calcium in aqueous solution. (December 2019) - Wu, Hechen; Chen, Hanhan; Fu, Minghui; Li, Rui; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract: Detection of trace metal ions in drinking as well as irrigation water is crucial in understanding their roles among living humans and animals. Herein, an organic PHBA-functionalized polyoxometalate (POM) derivative [N(CH3 )4 ]3 K2 Eu(PHBA)(H2 O)2 (α-PW11 O39 )]·7H2 O (1 ) (PHBA = p -hydroxybenzoic acid) was successfully synthesized which acts as a luminescent probe for selective sensing of chromium and calcium in aqueous solution. The aqueous solution photoluminescence properties of1 were carefully investigated, indicating PHBA ligand can sensitize the luminescence of Eu 3+ ion in1 . The time-resolved emission spectroscopy was also performed to authenticate the energy transfer from π-π* transition of PHBA group to Eu 3+ ion. The sensing properties of1 were performed on Cd 2+, Cr 3+, Ba 2+, K +, Li +, Pb 2+, Zn 2+, Al 3+, Ag +, Hg 2+, Co 2+, Sr 2+, Ca 2+, Na +, Mg 2+ ions in aqueous solution, and the photoluminescence intensity for Cr 3+ ion display a quenching phenomenon, whereas, Ca 2+ ion displays an enhancement signal in their photophysical behavior. The detection limits for detecting Cr 3+ and Ca 2+ ion were 1.423 μM and 0.676 mM, respectively. In the detection process of Cr 3+ ion, the values of quenching rate constant (Kq ) were varied from 4.34 × 10 6 L (mol s) −1 to 4.29 × 10 9 L (mol s) −1, which were lower than the value of the maximum scatter collision quenching constant (2.0 × 10 10 L (mol s) −1 ). The results reveal that the quenching mechanism between1 and Cr 3+ ion can be attributed to dynamic collision quenching mechanism. Furthermore, the active sites for sensing Cr 3+ and Ca 2+ ions also have been investigated, determining the different interaction mechanisms exist in detection of Cr 3+ and Ca 2+ ions in solution. Highlights: The PHBA functionalized Eu-POM was successfully synthesized. Organic PHBA components can sensitize the emission of emitting Eu 3+ ion. Energy transfer pathway in this Eu-POM has been studied. This Eu-POM can selectively detect Cr 3+ and Ca 2+ ions in solution.